Highly efficient genome editing in Bacillus subtilis via miniature DNA nucleases IscB - Jie Gao; Hengyi Wang; Jingtao Sun; Hongjie Tang; Yuhan Yang; Qi Li (Synthetic and Systems Biotechnology)
Existing CRISPR-based genome editing techniques for Bacillus subtilis (B. subtilis) are limited due to the large size of the cas gene. IscB, a recently reported DNA nuclease, is one-third the size of Cas9, making it a potential tool for genome editing; however, its application in B. subtilis remains unexplored. In this study, two IscB and enhanced IscB (enIscB)-based genome editing systems, named pBsuIscB and pBsuenIscB were established in B. subtilis SCK6, and their deletion efficiencies ranging from 13.3 % to 100 %. Compared to the pBsuIscB system, the pBsuenIscB system showed higher deletion efficiency, inducing the deletion of a large genomic fragment with a single ωRNA. Additionally, the pBsuenIscB system could integrate both single-copy and multi-copy mCherry genes in the B. subtilis SCK6 genome. Lastly, the pBsuenIscB system could efficiently conduct a second round of genome editing in B. subtilis SCK6. This study indicates that IscB can be used for genome editing in B. subtilis, enabling the efficient construction of engineered B. subtilis strains for large-scale biomolecule production.